Presenting a Sustainable Development Model Focus on Renewable Energy and Role of Government Policies - M. Jalili; S. Varedi; S. A. Jafari Kelarijani (Iranica Journal of Energy and Environment)
This study aimed to provide a clean energy-based growth model emphasizing public policy. The study's statistical population in the quantitative section in the first stage was the members of the fuzzy Delphi panel, consisting of 15 people from the most suitable group of experts regarding deep knowledge, breadth of view, and sufficient experience to achieve valid and accurate results. In the next step, the statistical population included all managers and experts of the Ministry of Energy in 2023-2024, totaling 327 people, using the Cochran formula through simple random sampling. The findings from the qualitative stage were analyzed using MAXQDA software. In the quantitative section, fuzzy Delphi tests, structural equation techniques, and the best-worst method were used with the help of SPSS, SmartPLS, Lingo, and Excel software. From the analysis of 15 interviews, 213 primary codes were extracted, 67 basic themes, and after categorization, ten organizing themes. The quantitative section's findings demonstrated that all correlations were acknowledged and that there was a meaningful route between all variables. Also, in prioritizing the indicators of the clean energy-based growth model with an emphasis on public policy, it was determined that the indicators of strategies for using clean energy were the priority, policies for using clean energy in the second priority, culturalization in society for using clean energy in the third priority, and the consequences of clean energy development in the fourth priority.